Advances in mobile augmented reality from user experience perspective: A review of studies - Irshad, S. (Springer Verlag, 2017)
Augmented Reality (AR) is maturing with the evolution in fields of computer and interactive graphics. Rapid advancements and growth of the mobile industry have allowed AR experiences to be delivered on mobile devices as well. When camera fitted mobile devices point towards a digital object to deliver AR experiences it creates design challenges due to Unique interaction style and Information presentation on Mobile Augmented Reality (MAR) applications. In order to overcome these design challenges, one needs to understand the User Experience (UX) of MAR. This paper reviews the advances in mobile augmented reality from UX perspective. This study aims to present a comprehensive and detailed review and will help in guiding the developers of MAR to focus on areas that need improvement. © Springer International Publishing AG 2017.